Managerial Recommendations for Enhancing Online Shopping Attitude and Intention of Consumers in Vietnam - Lu Phi Nga; Phan Thanh Tam (Ianna Journal of Interdisciplinary Studies)
Background: Global e-commerce, generally and in Vietnam, is growing strongly. The number of people participating in online shopping is increasing proportionately to the rate of Internet users and product information searches. Consumers mainly use smartphones to access the Internet and participate in online shopping.